Measuring procedures for surface evaluation of additively manufactured powder bed-based polymer and metal parts. (17th June 2020) - Heinl, M; Greiner, S; Wudy, K; Pobel, C; Rasch, M; Huber, F; Papke, T; Merklein, M; Schmidt, M; Körner, C; Drummer, D; Hausotte, T
Abstract: Powder bed-based additive manufacturing has become increasingly important for industrial applications. In the light of this, qualitative considerations such as the geometrical accuracy, the resulting mechanical properties, and the surface quality of additively manufactured parts must be taken into account. Optical measuring techniques such as confocal laser scanning microscopy, fringe projection and focus variation as well as profilometers are evaluated here, to determine the surface quality of powder bed-based manufactured parts. Even though these surface evaluation methods are established commercially, no standardized measuring procedure has yet been established. Within an experimental study the validity and accuracy of surface measurement methods are evaluated below, taking the limitations of each measurement system and the comparability of areal surface textures into account. The examinations are carried out with the powder materials EN-AW2024, Ti-6V-4Al and PA12, which are processed by electron beam melting, and laser beam melting of metals and polymers. Guidance for a consistent and comparable surface evaluation is thereby provided.